2019
DOI: 10.1111/clr.13498
|View full text |Cite
|
Sign up to set email alerts
|

In vivo accuracy of tooth surface reconstruction based on CBCT and dental MRI—A clinical pilot study

Abstract: Objectives Guided implant surgery (GIS) requires alignment of virtual models to reconstructions of three‐dimensional imaging. Accurate visualization of the tooth surfaces in the imaging datasets is mandatory. In this prospective clinical study, in vivo tooth surface accuracy was determined for GIS using cone‐beam computed tomography (CBCT) and dental magnetic resonance imaging (dMRI). Materials and methods CBCT and 3‐Tesla dMRI were performed in 22 consecutive patients (mean age: 54.4 ± 15.2 years; mean number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 42 publications
5
24
0
Order By: Relevance
“…For registration in implant planning, tooth surfaces are commonly used. The errors for in vivo tooth surface reconstructions derived from dental MRI and CBCT (mean error ± root mean square of dental MRI and CBCT 0.26 ± 0.1 and 0.1 ± 0.04 mm, respectively) were reported in a recent study [19]. This explains, at least in part, why accuracy was lower in our study than in Kühl et al…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…For registration in implant planning, tooth surfaces are commonly used. The errors for in vivo tooth surface reconstructions derived from dental MRI and CBCT (mean error ± root mean square of dental MRI and CBCT 0.26 ± 0.1 and 0.1 ± 0.04 mm, respectively) were reported in a recent study [19]. This explains, at least in part, why accuracy was lower in our study than in Kühl et al…”
Section: Discussionsupporting
confidence: 46%
“…This study has several methodological strengths. First, it made use of a previously established technique to visualize tooth surfaces within dental MRI [ 19 ]. As a result, it was possible to integrate dental MRI into an existing digital workflow without the need for additional software or time-consuming postprocessing steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, CEJ anatomical reference registration is usually di cult, though its impact on bone height measurements is to be around 0.01 mm, this is a lower difference than obtained with cusp tip (0.1 mm) as landmark [62]. These values are lower than the maximum errors reported for CBCT-derived tooth surfaces measures in vivo (± 0.2 mm) [63]. Also, this measurement variability at tooth surfaces level with CBCT, in vivo, is not that different from those observed for FAB thickness at CI, LI and C. In the present work, FAB measurement standard deviations in CI, LI, and C were around (± 0.2 to ± 0.29 mm)…”
Section: Discussionmentioning
confidence: 74%
“…In recent years, considerable technical advances have been made in the development and implementation of in vivo dental magnetic resonance imaging (dMRI) techniques (Hilgenfeld et al, 2017(Hilgenfeld et al, , 2018(Hilgenfeld et al, , 2019Juerchott et al, 2019;Ludwig et al, 2016;Sedlacik et al, 2016;Tymofiyeva et al, 2010). Recently, it was shown that a dMRI technique using intravenous gadolinium-based contrast agent (GBCA) enables the detection and classification of horizontal furcation defects in maxillary molars with high reliability and accuracy in vivo (Juerchott et al, 2020).…”
Section: Introductionmentioning
confidence: 99%